ANALISA PENDAPATAN NASIONAL PADA KOTA BATAM DI TAHUN 2018, 2019 DAN 2020 - Dewi Ratnasari; Jacelyin; Kevin Louis; Priscilla Paramitha Tanunjaya; Tri Julianto (Jurnal Cakrawala Ilmiah, 2022)
National or regional income is a very important aspect. This is a system used by the government to measure the level of economic income of a region or country over a certain period of time. This analysis was carried out to determine regional economic growth in the city of Batam during the Covid- 19 pandemic. From the discussion and analysis we can conclude that the GRDP of the city of Batam in 2019 will increase, but this does not last long because of the influence of the Covid-19 pandemic. In various regional budgets, there has also been a very drastic decline every year so that during the Covid-19 pandemic. From the discussion and analysis we can conclude that the GRDP of the city of Batam in 2019 will increase, but this does not last long because of the influence of the Covid-19 pandemic. In various regional budgets, there has also been a very drastic decline every year so that this has disrupted the economy of the city of Batam